PENGARUH KOMPENSASI, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA BADAN LAYANAN UMUM-UNIT PELAKSANA TEKNIS DINAS (BLU UPTD) TERMINAL MANGKANG - Rini Handayani, 11.05.51.0048 (Students Journal of Economic and Management, 2015)
Research on variable compensation, motivation, and discipline on the performance of the employee (Case Study on the Public Service Board-Technical Implementation Unit (BLU UPTD) Terminal Mangkang) took the 53 respondents with a significance level of 5%. In this study using purposive sampling sampling deliberate aim in accordance with the requirements of samples that need the appropriate requirements (properties, characteristics, traits, criteria) which reflects the population in this study is based on Staff Administration (Finance, HR, Sarpras, Operations, control, and General). Based on data analysis can be concluded as follows: Positive Discipline influential work of 4,363 with 0,000 significantly to the performance of employees. Motivation for 2,827 with a positive effect on the performance of a significant 0,007. Compensation for 2,091 and the positive impact significantly on the performance of employees 0,042 BLU UPTD Mangkang Terminal. Keywords: Compensation, Motivation, Work Discipline and Performance